2010
DOI: 10.1108/18363261011106858
|View full text |Cite
|
Sign up to set email alerts
|

Disclosing illness and disability in the workplace

Abstract: PurposeThis paper seeks to explore what disclosing illness and disability in the workplace means to workers with chronic illness and disabilities. It aims to argue that beginning analysis from the meanings of these workers contributes to a nuanced understanding of their situations; gaining this view requires knowing how individuals define their health as well as their meanings, risks, and dilemmas of disclosing illness and disability; understanding the employee's perspective and actions helps employers to make… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 34 publications
1
40
0
Order By: Relevance
“…Lengnick-Hall, Gaunt, and Kulkarni (2008) contend employers are concerned about how other able-bodied staff will react to staff with physical disability which influences their attitudes. However, it appears that if the worker themselves believes that their physical disability will not negatively impact on their performance then colleagues and managers are likely to be in agreement (Charmaz 2010). Roessler et al (2011) conducted a survey of 200 workers with multiple sclerosis (MS) in the United States.…”
Section: Physical Disabilitiesmentioning
confidence: 99%
“…Lengnick-Hall, Gaunt, and Kulkarni (2008) contend employers are concerned about how other able-bodied staff will react to staff with physical disability which influences their attitudes. However, it appears that if the worker themselves believes that their physical disability will not negatively impact on their performance then colleagues and managers are likely to be in agreement (Charmaz 2010). Roessler et al (2011) conducted a survey of 200 workers with multiple sclerosis (MS) in the United States.…”
Section: Physical Disabilitiesmentioning
confidence: 99%
“…Other options may include undertaking work at a lower level to assist with symptoms, or seeking work in a more understanding workplace. Charmaz (2010) found that where workers were established and valued within the organisation, employers were more likely to approve requests for accommodations. However, the possibility of discrimination or negative reactions of colleagues 'shapes how people manage information about their illness at work' (Beatty and Joffe, 2006: 186).…”
Section: Workplace Experiences: Managerial Attitudesmentioning
confidence: 99%
“…The issue of managerial attitudes towards employees with various types of disabilities is a topic which is increasingly under scrutiny by researchers both in Australia and overseas. Some notable papers on the topic include: Vickers (2012), Vickers (2003), Charmaz (2010), and Beatty and Joffe (2006). These studies show that the influences of others in the workplace, particularly managers, are pivotal to the retention of capable individuals with chronic illness or other disabilities in the workplace.…”
Section: Simplified Disclosure Contingency Pathwaysmentioning
confidence: 99%
See 2 more Smart Citations